2008
DOI: 10.1103/physreva.78.063804
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic black holes in a two-dimensional “photon fluid”

Abstract: Optical field fluctuations in self-defocusing media can be described in terms of sound waves in a 2D photon-fluid. It is shown that, while the background fluid couples with the usual flat metric, sound-like waves experience an effective curved spacetime determined by the physical properties of the flow. In an optical cavity configuration, the background spacetime can be suitably controlled by the driving beam allowing the formation of acoustic ergoregions and event horizons. An experiment simulating the main f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
104
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(109 citation statements)
references
References 30 publications
3
104
0
2
Order By: Relevance
“…This is of particular relevance, since only a linear dispersion guarantees superfluid behavior [10] and, in the context of analogue gravity, Lorentz invariance in the acoustic metric [7,19]. Translating these concepts into the language of optics [10],…”
Section: Theoretical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…This is of particular relevance, since only a linear dispersion guarantees superfluid behavior [10] and, in the context of analogue gravity, Lorentz invariance in the acoustic metric [7,19]. Translating these concepts into the language of optics [10],…”
Section: Theoretical Modelmentioning
confidence: 99%
“…As an alternative to actual flowing fluids, optical analogues obtained using laser beams propagating through nonlinear self-defocusing media or confined in nonlinear optical cavities have been proposed to create a photon fluid with the desired flow pattern. In these systems the fluid properties can be controlled through the phase and intensity of the incident optical field, as well as by the refractive index profile and the structural boundaries of the medium [7][8][9]. For example, a theoretical framework for photon fluids [1,7,8,10,11] has shown that sound-like excitations experience a curved spacetime, and hence are promising models for analogue gravity experiments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the medium filling the space between the mirrors has a suitable Kerr nonlinearity, significant binary photon-photon interactions appear, with a strength proportional to the nonlinear polarizability χ (3) . In high-energy physics, such lightlight scattering processes can occur in the QED vacuum via the creation of virtual electron-positron pairs, as described by the so-called Heisenberg-Euler Lagrangian 2 .…”
Section: Introduction: Quantum Fluids Of Lightmentioning
confidence: 99%
“…After a series of pioneering experiments demonstrating superfluidity and superfluid hydrodynamic behaviors [34][35][36], it was soon proposed that these novel quantum many-body systems are also able to host analog black-hole horizons [37][38][39][40][41]. Recently, It consists of a laterally patterned semiconductor microcavity device in the form of a long one-dimensional photonic wire oriented along the x direction, and with a micrometer-sized x-dependent lateral profile designed in a way to facilitate observation of analog Hawking effects.…”
Section: Introductionmentioning
confidence: 99%